Incorporation of a Non-Conventional Liana Tetracapidium Conophorum Seed Oil Cake in Based - Diets of Indigenous Batéké Chicks Raised in Close Confinement in Congo - Adzona, P.P.; Mopoundza, P.; Ngouama, A. DandoU; Bati, J.B.; Ntsoumou, M.V.; Saya Ngouonomba, H.J.; Akouango, P.; Banga-Mboko, H. (European Scientific Journal, ESJ, 2024)
The indigenous Batéké hen (Gallus gallus) has low productivity due to various constraints such as feeding sources. The aim of this study was to improve the productivity of the local hen using a new local protein source: Tetracarpidium conophorum meal. Ninety-six chicks 21-day old from the local population were randomized into 3 groups of 32 birds each (TC0, TC4 and TC6), with one replicate. Tetracarpidium conophorum meal was incorporated into groupsTC4 (4% Tcconophorum oil cake and 11% soya oil cake), TC6 (6% T.conophorum oil cake and 9% soya oil cake) whereas TC0 served as a control group (0% T.conophorum meal and 15% soya oilcake). The experiment started at 3 weeks and lasted at 20 weeks of age. Chickens were fed ad libithum and had free access to drinkers. The treatment decreased mortality rate (3.12 % versus 9.3), On the other hand the treatment improves significantly (p ˂ 0.05). feed intake (56.8 vs 60.1g per day), feed conversion (6.5 vs 5.7), and carcass yield (65.8 % vs 71.3 %). The final body weight at 20 weeks of age was low in all groups (1.200g versus 1300g) at 4% of incorporation of T. conophorum meal. Meat yield. This study indicated to incorporate T.conophorum oil cake at 4% and reducing soya oil cake from 15% to 11%) in a small scale poultry farming in Congo.